USPIO‐loaded red blood cells as a biomimetic MR contrast agent: a relaxometric study. (6th March 2014) - Boni, Adriano; Ceratti, Davide; Antonelli, Antonella; Sfara, Carla; Magnani, Mauro; Manuali, Elisabetta; Salamida, Sonia; Gozzi, Alessandro; Bifone, Angelo
<x xml:space="preserve">Abstract</x> Red blood cells (RBCs) loaded with iron oxide nanoparticles have been proposed as biomimetic constructs with long half‐life (ca. 20 days) in the blood compartment and potentially interesting properties (such as relaxivity) as intravascular contrast agents for magnetic resonance imaging. However, the encapsulation of nanoparticles into RBCs might affect their magnetic properties and relaxivity, which may be significantly different from the native suspension. Here, we present a relaxometric study of P904, a novel ultra small iron oxide nanoparticle developed by Guerbet, enclosed in human RBCs. We measured longitudinal (r1) and transverse (r2) relaxivity over a wide range of Larmor frequencies (0.01–300 MHz) in samples of P904‐loaded RBCs, and in control samples with P904 nanoparticles dispersed in blood. Internalization of P904 into RBCs resulted in smaller r1, and in a very high r2/r1 ratio (232) at the highest field. Moreover, a shift of the Curie peak to high fields was observed in P904‐loaded RBCs, possibly the result of nanoparticle size selection caused by the internalization process. High r2 relaxivity together with a high r2/r1 ratio and a very long blood half‐life make P904‐loaded RBCs a promising blood‐pool negative contrast agent for MR diagnostic applications. Copyright © 2014 John Wiley & Sons, Ltd.